The Use of Digital Communication Technologies in Higher Education Learning: Prospects and Challenges - Akil, Muhammad Anshar; Arsal, Andi Faridah; Andi Syahraeni (Jurnal Dakwah Tabligh, 2025)
Abstract The use of digital communication technology in learning in higher education is a mandate of the education law regarding e-learning. The purpose of this study is to analyze the characteristics of digital communication technology, types of learning applications, prospects and challenges of digital learning in higher education. The results of the study indicate that digital learning is carried out synchronously or asynchronously using hardware, software, internet, and database devices. Learning communication technology is digital, interactive, hypertextual, global, virtual, and simulation. Digital learning uses websites, learning management systems, classrooms, videoconferencing, social media, and messaging applications such as WA. The prospects for digital learning are more flexible learning places, dynamic time, reduced transportation costs, materials available at all times, developing knowledge and skills. Meanwhile, the challenges faced are: dependence on internet quality, cost of purchasing quotas, need for communication devices, participant responsibility, lecturer creativity, data privacy and ethics. Therefore, digital-based learning needs to maximize all available facilities and be able to overcome the obstacles faced. Various media and applications available need to be used in an integrated manner, including synchronous and asynchronous learning (blended learning). By understanding the character of technology and using various media synergistically, digital learning runs effectively to achieve learning goals in higher education. Keywords: Digital communication technology, digital learning, higher education